2022
DOI: 10.1038/s41598-022-14329-0
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: Strontium doped bioglass incorporated hydrogel-based scaffold for amplified bone tissue regeneration

Abstract: Repairing of large bone injuries is an important problem in bone regeneration field. Thus, developing new therapeutic approaches such as tissue engineering using 3D scaffolds is necessary. Incorporation of some bioactive materials and trace elements can improve scaffold properties. We made chitosan/alginate/strontium-doped bioglass composite scaffolds with optimized properties for bone tissue engineering. Bioglass (BG) and Sr-doped bioglasses (Sr-BG) were synthesized using Sol–Gel method. Alginate-Chitosan (Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 90 publications
(107 reference statements)
1
24
0
Order By: Relevance
“…Furthermore, an in vitro study researched by Baheiraei et al [ 70 ] showed that gelatin-BGs/Sr scaffolds can inhibit the vitality of Escherichia coli and some Staphylococcus aureus, thereby preventing infection and improving bone regeneration. Sr-BGs with high mechanical strength and better cell differentiation efficiency are a suitable choice for bone defect repair materials [ 71 ]. Fiorilli et al [ 72 ] confirmed the osteogenic effect of Sr incorporation into BGs by analyzing the expression of COLⅠa1, RANKL, OPG, and ALP.…”
Section: Biomaterials Compound With Srmentioning
confidence: 99%
“…Furthermore, an in vitro study researched by Baheiraei et al [ 70 ] showed that gelatin-BGs/Sr scaffolds can inhibit the vitality of Escherichia coli and some Staphylococcus aureus, thereby preventing infection and improving bone regeneration. Sr-BGs with high mechanical strength and better cell differentiation efficiency are a suitable choice for bone defect repair materials [ 71 ]. Fiorilli et al [ 72 ] confirmed the osteogenic effect of Sr incorporation into BGs by analyzing the expression of COLⅠa1, RANKL, OPG, and ALP.…”
Section: Biomaterials Compound With Srmentioning
confidence: 99%
“…Antibacterial systems can enhance the tissue regeneration process by inhibiting pathogenic microorganisms 28,29 . The antibacterial activity of the double-layered nanofibrous mat with and without SSD against S. aurous and P. aeruginosa is shown in Fig.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Zare et al reported strontium-doped BAG nanofibers for bone tissue engineering applications . Manoochehri et al prepared a strontium-doped bioglass-incorporated hydrogel-based scaffold for amplified bone tissue regeneration . However, these BAG-based hydrogel scaffolds often require invasive surgical procedures, excellent defect margin adaptation, and complete defect filling owing to their nature of non-injectability…”
Section: Introductionmentioning
confidence: 99%